Empowerment of Sharia-Based Village Owned Enterprises (BUMDes) - Sujana, I Wayan; Ridzal, Nining Asniar (Lembaga Riset dan Inovasi Masyarakat Madani, 2023)
Lawela Selatan Village, located in South Buton Regency, is a predominantly Muslim community that also receives government funding. To sustain the village's economy, the establishment of Village Owned Enterprises (BUMDes) has been crucial. Given the growing prominence of Islamic economics in Indonesia's business landscape, it is vital to explore its application within BUMDes. This endeavor aims to equip all participants, especially BUMDes management, with fundamental knowledge and comprehension of Islamic economics. The implementation of charitable activities proceeded smoothly without any notable obstacles. The BUMDes in South Lawela Village, Batauga Subdistrict, South Buton Regency, is known as BUMDes Cahaya Baru and encompasses service-oriented enterprises such as equipment rental, wedding decoration, building materials, trading companies, and the tourism sector. Furthermore, there are untapped regional potentials that present promising development opportunities. Prioritizing the development of local potentials is of utmost importance, particularly in reinforcing BUMDes based on the Sharia system due to the predominantly Muslim population. The objective of the service team is to impart knowledge to BUMDes management, specifically focusing on the advancement of Sharia-based BUMDes.